PENGEMBANGAN E-MODUL BERBASIS TPACK MENGGUNAKAN FLIP PDF PROFESSIONAL PADA MATERI KELILING BANGUN DATAR KELAS V SEKOLAH DASAR 008 SUNGAI KUNJANG - Elisabet Kerokong; Andi Asrafiani Arafah; Makmun; Sukriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research and development focuses on the problems faced by students in understanding the material, particularly the perimeter of flat shapes. This problem arises due to the limited use of diverse and engaging learning resources, as well as the low use of technology. This study aims to determine the development process of an e-module, the feasibility of the e-module according to media, material, and language experts, and the practicality of the TPACK-based e-module for fifth-grade students. This research applies the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation, and involves evaluation from media, material, and language experts. The results show that the e-module meets the very feasible category with an assessment of 92.86% from media experts, 84.44% from material experts, and 86.67% from language experts. Meanwhile, for practicality testing, it was conducted in two phases: the first was a small group test involving six students, which obtained a score of 98.63% with a very practical category, while the large group test involving 24 students obtained a score of 94.31% with a very practical category.